STRATEGI PENGEMBANGAN USAHATANI JAGUNG MANIS DI KECAMATAN PURWOHARJO KABUPATEN BANYUWANGI - Putra, Ade Pradana; Prayuginingsih, Henik; Ridho, Atkok Ainur (Jurnal Mahasiswa Entrepreneurship (JME), 2022)
Sweet corn (Zea mays saccharata Sturt) is a food crop that is in demand by the public because it has a sweeter taste than ordinary corn, has high economic value and has a faster harvest time. In this case, the objectives of this research are (1) farming business development strategies in Purwoharjo District. This research uses descriptive and quantitative methods. The research sample consisted of 40 farmers. Data were analyzed using (1) SWOT analysis. The research results show that (1) the strategy for developing sweet corn farming is Strengths - Opportunity (S-O) including (1) optimizing the existing workforce to improve sweet corn farming (2) With facilities and Infrastructure that is not yet supported should be further improved to make things easier for farmers